ANALISIS PERILAKU SEKSUAL PADA REMAJA DI SMP YP UNILA BANDAR LAMPUNG PROVISI LAMPUNG TAHUN 2018 - Putri Azzahroh; Sri Utami Afriani (Jurnal Ilmu dan Budaya, 2018)
Adolescence is a transitional period between childhood and adulthood, which begins at the time of sexual maturity, which is between 11 or 12 years to 20 years, namely before adulthood. Sexual behavior is all behavior driven by sexual desire starting from feeling attracted to dating behavior, dating, and intercourse. The research results of the Indonesian Ministry of Health in2016 showed that 35.9% of teenagers had friends who had premarital sex and 6.9% of respondents had premarital sex. This study aims to determine factors related to sexual behavior on adolescents in SMA YP Unila, Tanjung Karang, Bandar Lampung in 2018. This research is an observational study with cross-sectional design that uses quantitative methods. The measurement through scientific calculations is derived from 211 samples of respondentswho were asked to answer the number of questions about the survey to determine the frequency and percentage of respondents' responses. The behaviors of adolescent at SMA YP Unila High School that are categorized as bad are 131 respondents (62.1%) and those who are categorized as good are 80 respondents (37.9%). The results shows that there is a relationshipbetween behavior and factors related to sexual behavior; they are knowledge factors (p-value 0.036, OR 1.917), attitudes (p-value 0.031, OR 1.947), sources of information (p -value 0.002, OR 2,508), and association (p-value 0.006, OR 2,279). The most influential factors to sexual behavior are sources of information with OR 2.50.